Targeted inhibition of GATA-6 attenuates airway inflammation and remodeling by regulating caveolin-1 through TLR2/MyD88/NF-κB in murine model of asthma. (July 2016) - Fang, Ping; Shi, Hong-yang; Wu, Xiao-ming; Zhang, Yong-hong; Zhong, Yu-jie; Deng, Wen-jing; Zhang, Yu-ping; Xie, Mei
Highlights: The expression of GATA-6 and Cav-1 in OVA-induced asthma model. Knockdown of GATA-6 alleviated airway inflammatory in OVA-induced asthma model. Knockdown of GATA-6 relieved airway remodeling in OVA-induced asthma model. TLR2/MyD88/NF-κB contributes to regulation of GATA-6 on airway inflammation and remodeling. Abstract: The purpose of this study was to evaluate the effects of GATA-6 on airway inflammation and remodeling and the underlying mechanisms in a murine model of chronic asthma. Female BALB/c mice were randomly divided into four groups: phosphate-buffered saline control (PBS), ovalbumin (OVA)-induced asthma group (OVA), OVA+ siNC and OVA+ siGATA-6. In this mice model, GATA-6 expression level was significantly elevated and the expression in Caveolin-1 (Cav-1) inversely correlated with the abundance of GATA-6 in OVA-induced asthma of mice. Silencing of GATA-6 gene expression upregulated Cav-1 expression. Additionally, downregulation of GATA-6 dramatically decreased OVA-challenged inflammation, infiltration, and mucus production. Moreover, silencing of GATA-6 resulted in decreased levels of immunoglobulin E (IgE) and inflammatory mediators and reduced inflammatory cell accumulation, as well as inhibiting the expression of important mediators including matrix metalloproteinase (MMP)-2 and MMP-9, TGF-β1, and a disintegrin and metalloproteinase 8 (ADAM8) and ADAM33, which is related to airway remodeling. Further analysis confirmed that silencing of GATA-6 attenuated OVA-induced airway inflammation and remodeling through the TLR2/MyD88 and NF-κB pathway. In conclusion, these findings indicated that the downregulation of GATA-6 effectively inhibited airway inflammation and reversed airway remodeling via Cav-1, at least in part through downregulation of TLR2/MyD88/NF-κB, which suggests that GATA-6 represents a promising therapeutic strategy for human allergic asthma.